Antecedent and Consequence of ICT Utilization in Education: Voices from Private University Lectures In Indonesia - Kainama, Maryoni Stevanny; Latuserimala, Gerald (Jurnal Pendidikan Progresif, 2022)
Antecedent and Consequence of ICT Utilization in Education: Voices from  Private University Lecturers  In Indonesia. In the last few years, the adoption of information technology in education environment in Indonesia still low. The  utilization of information technology was expected giving a positive influence to lecturer’s performance. This research tested the factors empirically as antecedent in utilization of information technology such as social factor, affect, complexity, job fit, long term consequence, facilitating condition, and consequence of utilization of information technology to performance. The information technology in this research limited on using personal computer which supported the lecturer’s activity. Sampels in this research were private university’s economics lecturers in Indonesia. The lecturers of private universities in Maluku considered to represent private university’s lectures outside of Java and private university’s lecturers in Malang represented private university’s lecturers who was created to a control group. The result of this research found that private university’s lecturers in Indonesia perceived that utilization of information technology significantly gave positive influence to their performance. While utilization of information technology for half of lecturers were not influenced by six tested factors, and the others perceived that utilization of information technology were influenced by social factor, affect and facilitating condition Keywords: social factor, affect, complexity, job fit, long term consequence, facilitating condition.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202203